Determining the training needs of teacher educators in some colleges of education in the Eastern Cape Province for outcomes based education - Matsheke, Vuyisa Valentia (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Phil.) -- University of Stellenbosch, 1999.